Lipid profile in systemic lupus erythematosus: study from a tertiary teaching hospital of Eastern India - Dakua, Simanchala; Behera, Manoranjan; Panda, Jayant Kumar; Padhi, Prabhat Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Dyslipidemia is an independent modifiable risk factor for coronary artery disease. Patients with systemic lupus erythematosus (SLE) have dyslipidemia and accelerated atherosclerosis; however, there is paucity of published data on the lipid profile in patients with SLE in Eastern India. This study was done to assess the prevalence and abnormality of lipid profile in patients with SLE admitted to a tertiary care teaching hospital in Eastern India. Methods: This was a hospital based prospective study evaluating SLE patients admitted to a tertiary care institution in Eastern India. 101 patients with SLE admitted consecutively and 100 age and sex matched controls were enrolled for study. Fasting total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were measured in plasma whereas very low-density lipoprotein cholesterol (VLDL-C) was calculated. Statistical analysis was done using the standard statistical techniques. Results: Out of 101 patients of SLE, 97 were female and 4 were of male gender. The age of the patients ranged from 15 to 47 years with a mean of 27.17 (±8.4) years. Dyslipidemia was found in 58(57.4%) patients. Hypercholesterolemia was found in 23 (22.7%), hypertriglyceridemia in 55 (54.4%), raised LDL-C in 24 (23.7%) cases. Raised TC, TG, and LDL-C was found in 18 (17.8%), and raised TC, TG, LDL-C and low HDL-C was found in 9 (8.9%) cases. There was significant increase in serum cholesterol, triglyceride and VLDL-C while decrease in HDL-C in SLE patients than controls (p <0.001). Statistically no difference in lipid profile was found in between groups of SLE receiving steroid and without steroid. Conclusions: Abnormal lipid profiles are very common in patients with SLE, though the patients are very young. Control of dyslipidemia can favourably affect cardiovascular related morbidity and mortality.